SUITABILITY OF EARLY MATURING SUGARCANE GENOTYPES FOR DELAYED HARVESTING - U , VIJAYA BHASKAR REDDY; J , SATYAPRIYA LALITHA (The Journal of Research ANGRAU, 2026)
An experiment in sugarcane was conducted during 2021-22 to 2023-24 in strip-plot designwith three replications at Sugarcane Research Station, Vuyyuru. Sugarcane clones viz., 2012 V67, 2012 V 123, 2013 V 126 and 2003 V 46 were tested for delayed harvesting. Significantlymore number of tillers per hectare were recorded by check variety 2003 V 46 (1,03,085) whichwas statistically at par with 2012 V 67 (97,154) and  2013 V 126 (94,316) at 90, 180 and 240days after planting. Millable canes were also significantly higher with 2003 V 46. Significantlyhigher yield was recorded by 2003 V 46 (105.06 t/ha) followed by 2012 V 67 (96.42 t/ha) and2013 V 126 (91.24 t/ha). Significantly more sucrose  percent was recorded with  2003 V 46(20.15%) which was followed by 2012 V 123 (20.05%), 2012 V 67 (19.32%) and 2013 V 126(19.18%).The variety 2003 V 46 recorded significantly more commercial cane sugar  (14.5 %)which was statistically at par with 2012 V 123 (14.4%).The study clearly revealed that, the highercane yield, per cent sucrose  and commercial cane sugar were obtained with check variety  2003V 46 over other new genotypes tested in this study.